Joint seals for hydraulic structures in severe climates - Mirza, Jahangir (Journal of Civil Engineering and Management, 2014)
This paper presents laboratory test data on 21 joint seals: 10 field-moulded sealants (FMS; 1- and 2-components polyurethanes, polysulphides, silicones, etc.) and 11 preformed seals (neoprene, silicone, high-density open-cell and low-density closed-cell foams, etc.). The aim was to evaluate their performance in submerged, partially submerged and essentially dry conditions in extremely severe climates. These seals were tested on cement mortar substrates as well as on steel substrates. The tests carried out on FMS were: adhesion-in-peel strength, compression-extension cycling at severe temperatures, Shore A hardness, weatherability and modulus of elasticity, etc. On preformed seals, the tests conducted were weatherability, % recovery and load deformation behaviour, etc. Conclusions, recommendations and the specific suitability of joint seals with cement mortar and steel substrates are reported. The general conclusion is that even though the joint seals evaluated had similar base chemical constituents, they showed variable results. Their properties and characteristics differ from one manufacturer to others, indicating that prior knowledge about their performance is essential to the user. Furthermore, the published data on the performance of seals used in hydraulic structures situated in severe climatic conditions is sparse. It is recommended that utilities publish as much information as possible to help others.